2018
DOI: 10.3390/healthcare6030085
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and Protocol for a Randomized Controlled Trial Comparing Fast versus Slow Weight Loss in Postmenopausal Women with Obesity—The TEMPO Diet Trial

Abstract: Very low energy diets (VLEDs), commonly achieved by replacing all food with meal replacement products and which result in fast weight loss, are the most effective dietary obesity treatment available. VLEDs are also cheaper to administer than conventional, food-based diets, which result in slow weight loss. Despite being effective and affordable, these diets are underutilized by healthcare professionals, possibly due to concerns about potential adverse effects on body composition and eating disorder behaviors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 8 publications
(32 citation statements)
references
References 91 publications
(100 reference statements)
0
32
0
Order By: Relevance
“…The full inclusion and exclusion criteria and our rationale for these have been detailed in our published protocol. 27 The trial was conducted in accordance with the Declaration of Helsinki 28 and Good Clinical Practice guidelines. 29 All participants provided written informed consent prior to participation.…”
Section: Methodsmentioning
confidence: 99%
“…The full inclusion and exclusion criteria and our rationale for these have been detailed in our published protocol. 27 The trial was conducted in accordance with the Declaration of Helsinki 28 and Good Clinical Practice guidelines. 29 All participants provided written informed consent prior to participation.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were enrolled in the TEMPO Diet Trial ( T ype of E nergy M anipulation for P romoting optimum metabolic health and body composition in O besity, Australian New Zealand Clinical Trials Registry Number 12612000651886), a randomized controlled trial investigating the effects of weight loss via severe versus moderate dietary energy restriction on a range of physiological and psychological variables. Participant eligibility was described in full elsewhere [26]. In brief, eligible participants were ambulatory, sedentary (<60 min of physical activity per week), and had been weight stable for at least six months (±2 kg).…”
Section: Methodsmentioning
confidence: 99%
“…Participants completed a total of four questionnaires for this study: two questionnaires measuring eating disorder behaviors (the Eating Disorder Examination Questionnaire, EDE-Q, and the Loss of Control over Eating Scale, LOCES) and two questionnaires assessing mindfulness (the Five-Facet Mindfulness Questionnaire, FFMQ, and the Langer Mindfulness Scale, LMS). These questionnaires were administered two weeks prior to commencement of the intervention during a face-to-face appointment at our clinical research facility (for more details, refer to our previous publication [26]). Data from the LOCES were only available for 88 participants, as we started administering this scale after data collection had begun.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the study protocol and 12-month intervention for the severely energy-restricted arm of the TEMPO Diet Trial have been reported in detail previously. [23][24][25] Briefly, participants were randomized to 4 months (16 weeks) of severe energy restriction of 65% to 75% relative to estimated energy expenditure, using a total meal replacement diet, followed by moderate energy restriction of 35% to 25% for an additional 8 months (36 weeks). The total meal replacement products used in the severely energy-restricted diet provided between 2,630 (630 kcal) and 3,260 kJ (780 kcal) per day in this group of participants.…”
Section: Severely Energy-restricted Dietmentioning
confidence: 99%